2014
DOI: 10.1124/dmd.113.056770
|View full text |Cite
|
Sign up to set email alerts
|

Translational Pharmacokinetic Modeling of Fingolimod (FTY720) as a Paradigm Compound Subject to Sphingosine Kinase-Mediated Phosphorylation

Abstract: A complicating factor in the translational pharmacology of sphingosine 1-phosphate agonists is that they exert their pharmacological effect through their respective phosphate metabolites, which are formed by the enzyme sphingosine kinase (S1PHK). In this investigation, we present a semimechanistic pharmacokinetic model for the interconversion of S1PHK substrates and their respective phosphates in rats and humans with the aim of investigating whether characterization of the rate of phosphorylation in blood plat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Moreover, as the major fingolimod phosphorylating enzyme,sphingosine kinase 2, is mostly found in the nuclear and membranous compartments , fingolimod‐phosphate was dissolved in the pipette solution, rather than in the bath solution, reflecting its preferential intracellular distribution in native cells. Previous clinical studies have shown that fingolimod‐phosphate plasma concentration at steady state after oral administration of fingolimod 0.5 mg daily was 1–2 ng/mL (3–6 nmol/L) . Interestingly, Meno‐Tetang et al have shown that in rats, oral administration of fingolimod leads to concentrations of the drug at least 10 times higher in the heart than in venous blood.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, as the major fingolimod phosphorylating enzyme,sphingosine kinase 2, is mostly found in the nuclear and membranous compartments , fingolimod‐phosphate was dissolved in the pipette solution, rather than in the bath solution, reflecting its preferential intracellular distribution in native cells. Previous clinical studies have shown that fingolimod‐phosphate plasma concentration at steady state after oral administration of fingolimod 0.5 mg daily was 1–2 ng/mL (3–6 nmol/L) . Interestingly, Meno‐Tetang et al have shown that in rats, oral administration of fingolimod leads to concentrations of the drug at least 10 times higher in the heart than in venous blood.…”
Section: Methodsmentioning
confidence: 99%
“…Because the PK of BMS‐986166 cannot practically be evaluated after intravenous administration and BMS‐986166‐P cannot be directly administered, it was not possible to simultaneously estimate parameters describing BMS‐986166 and BMS‐986166‐P PK or develop a more mechanistic and physiologically representative model as was done for fingolimod 30 . In particular, the relative fractional conversion of BMS‐986166 to BMS‐986166‐P occurring presystemically (eg, in the gastrointestinal tract) vs that occurring after absorption (eg, in the liver) was not identifiable based on the available data.…”
Section: Discussionmentioning
confidence: 99%
“…For ponesimod, only the mean of baseline‐corrected HR following the first dose of active drug or placebo was available. The maximum HR effect of the active treatment relative to placebo at doses producing approximately 70% reduction in ALC varied across molecules and ranged from approximately –21 to –6.5 bpm for siponimod, 17,18 from –18 to –12 bpm for ponesimod, 15,16 –11 to –6 bpm for fingolimod, 12,30 from –14 to –13 bpm for GSK2018682, 13 and from –8 to –6 bpm for ozanimod 14 . Ceralifimod provided only 56% reduction in ALC at the highest reported dosage (ie, 0.1 mg/day) and induced up to –8 bpm HR effect over placebo 12 .…”
Section: Discussionmentioning
confidence: 99%
“…Due to slow absorption and high binding to plasma proteins [48], FTY720 half-life in rat was found to be ~20 hr [49] with single IV doses ranging from 0.3 to 4 mg/kg, and at ~7 days in human after a single oral doses of 1 mg FTY720 [50]. In comparison to FTY720, neither of the new analogues was phosphorylated and had markedly shorter half-lives (less than 2 hr, for FTY720-Mitoxy) than the parent compound.…”
Section: Discussionmentioning
confidence: 99%